2016
DOI: 10.5430/afr.v5n4p147
|View full text |Cite
|
Sign up to set email alerts
|

The Extent and Determinants of Voluntary Disclosures in Annual Reports: Evidence from Banking and Finance Companies in Sri Lanka

Abstract: Corporate disclosures are essential for every stakeholders. Hence, in excess of mandatory disclosures companies are voluntary disclosed information. The voluntary disclosure level is different from company to company and there may be some factors which are affect to this variation. Therefore, the objectives of this study are to identify the extent of voluntary disclosure level and its determinants. In order to achieve these objectives the study develop a voluntary disclosure index including 83 items and the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…However, the results of prior studies that investigated the relationship between leverage and voluntary disclosure were not consistent. Some studies found a positive and significant relationship between firm leverage and voluntary disclosure (Abeywardana & Panditharathna, 2016;Kolsi, 2012;Lan et al, 2013;Sharma & Davey, 2013;Xiao, Yang, & Chow, 2004), whereas a significant negative association between firm leverage and voluntary disclosure was found by other studies (Birjandi & Hakemi, 2015;Elfeky & Nasiri, 2017;Sehar et al, 2013). On the other hand, the studies were undertaken by Owusu-Ansah (1997), Alves, Rodrigues, & Canadas (2012), Uyar et al, (2013) and Hieu & Lan (2015) found that no significant relationship between firm leverage and voluntary disclosure.…”
Section: Literature Reviewmentioning
confidence: 84%
See 3 more Smart Citations
“…However, the results of prior studies that investigated the relationship between leverage and voluntary disclosure were not consistent. Some studies found a positive and significant relationship between firm leverage and voluntary disclosure (Abeywardana & Panditharathna, 2016;Kolsi, 2012;Lan et al, 2013;Sharma & Davey, 2013;Xiao, Yang, & Chow, 2004), whereas a significant negative association between firm leverage and voluntary disclosure was found by other studies (Birjandi & Hakemi, 2015;Elfeky & Nasiri, 2017;Sehar et al, 2013). On the other hand, the studies were undertaken by Owusu-Ansah (1997), Alves, Rodrigues, & Canadas (2012), Uyar et al, (2013) and Hieu & Lan (2015) found that no significant relationship between firm leverage and voluntary disclosure.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Older firms with more experience are probably to disclose more information in their annual reports to improve their image and reputation in the market (Akhtaruddin, 2005). Most of the results of the empirical study show that there is a positive relationship between firm age and voluntary or mandatory disclosure (Abeywardana & Panditharathna, 2016;Elfeky & Nasiri, 2017;Hossain & Hammami, 2009;Owusu-Ansah, 2005;Sehar, Bilal, & Tufail, 2013). However, Hossain & Reaz (2007) and Akhtaruddin (2005) found no significant relationship.…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…The valid data was 200 observations and analyzed using panel data analysis. The analysis explained that there were positive associations between VD and profitability from Banking and Finance Companies in Sri Lanka (Abeywardana and Panditharathna, 2016).…”
Section: -4 Voluntary Disclosure and Bank Profitabilitymentioning
confidence: 96%